(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information on how, using questionnaires, to determine the popularity of various sections of the school curriculum in the areas of physical culture, physical activity, interest in physical culture and sports. The dependence of the level of physical activity and the level of health of students is considered. The influence of their physical activity on the levels of academic performance and morbidity is proved.